Size Dependence of Pt Catalysts for Propane Dehydrogenation: from Atomically Dispersed to Nanoparticles - Zhang, Wei; Wang, Haizhi; Jiang, Jiawei; Sui, Zhijun; Zhu, Yian; Chen, De; Zhou, Xinggui (ACS catalysis, 2020)
The structure–performance relationship is a critical fundamental issue in heterogeneous catalysis, and the size-dependent structure sensitivity of catalytic reactions has long been researched in catalysis. Yet it remains elusive for most of the reactions in a full-size range, from a single atom and subnanometer clusters to nanoparticles. Herein, we report complete size dependence of Pt catalysts used in propane dehydrogenation in terms of activity, selectivity, and stability due to coke formation. The turnover frequency (TOF) of the atomically dispersed Pt/Al2O3 catalyst was approximately 3-fold and 7-fold higher than the subnanometer-sized clusters and the nanoparticles, respectively. A canyon- shaped size dependence of the propene selectivity was observed with a bottom at about 2 nm of Pt particle size. The subnanometer-sized clusters have opposite size dependence of the propene selectivity compared to nanoparticles. Both atomically dispersed Pt and large Pt nanoparticles possess high propene selectivity. The atomically dispersed platinum centers with a positive charge dramatically enhanced the activity, weakened propylene adsorption, and prevented its deep dehydrogenation. Besides, the absence of multiple Pt–Pt sites effectively inhibited undesired side reactions (e.g., C–C cracking), thus improved propylene selectivity and stability. This work demonstrates the promising application of a supported atomically dispersed Pt catalyst for highly selective dehydrogenation of propane.